Post-weaning cranial ontogeny in two bandicoots (Mammalia, Peramelomorphia, Peramelidae) and comparison with carnivorous marsupials - Flores, David Alfredo (2013)
The ontogeny of the skull has been studied in several marsupial groups such as didelphids, microbiotheriids, and dasyurids. Here, we describe and compare the post-weaning ontogeny of the skull in two species of bandicoots, Echymipera kalubu (Echymiperinae) and Isoodon macrourus (Peramelinae), analyzing specific allometric trends in both groups, describing common (and specific) patterns, and discussing them on functional and phylogenetic grounds. Growth patterns were analyzed both qualitatively and quantitatively, including bivariate and multivariate analyses of allometry. We also evaluated character transformation and phylogenetic signals of the allometric patterns in several groups of marsupials and some placentals. We identified morphological changes between juvenile and adult stages in both species of peramelids, many related to the development of the trophic apparatus. Notable differences were detected in the patterns of growth, suggesting divergences in ontogenetic trajectories between both species. Both bivariate and multivariate methods indicate that positive allometries in E. kalubu apply to longitudinal dimensions, whereas in I. macrourus, positive allometries are restricted to vertical dimensions of the skull. The comparison of the allometric trends of two bandicoots with previously studied taxa reveals that although peramelids exhibit a particularly short gestation period and divergent morphology compared to other marsupials, their pattern does not show any particular trend. Some allometric trends seem to be highly conserved among the species studied, showing weak phylogenetic signal. Marsupials in general do not show particular patterns of post-weaning skull growth compared with placentals.